Choroidal thickness under pilocarpine versus cyclopentolate - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Panda-Jonas, Songhomitra; Mustafina, Gulshat R.; Jonas, Jost B. (Scientific reports, 2025)
Bruch´s membrane (BM) is firmly connected posteriorly to the optic nerve head through the peripapillary choroidal border tissue, and anteriorly through the longitudinal ciliary muscle to the scleral spur. We assessed, whether a difference in the contractile state of the ciliary muscle influences the position of the posterior BM by lifting the posterior BM pole, i.e., induces changes in the subfoveal choroidal thickness (SFCT). Healthy young adult individuals received one drop of cyclopentolate 1% into their right eyes and one drop of pilocarpine 1% into their left eyes. Using optical coherence tomography (OCT), three examiners measured independently SFCT and choroidal thickness in the fundus midperiphery at baseline and 30 min after eye drop instillation. The study included 21 healthy individuals (age:21.9 ± 2.6 years; range:15.7-25.8 years; axial length:24.4 ± 1.2 mm). In the right eyes, SFCT changed by 8.7 ± 34.9 μm (examiner 1), -2.9 ± 18.6 μm (examiner 2), and 10.5 ± 21.8 μm (examiner 3), respectively, and the midperipheral choroidal thickness changed by -10.6 ± 25.9 μm (examiner 1), 0.9 ± 17.5 μm (examiner 2), and 4.2 ± 24.7 μm (examiner 3), respectively, without significant differences between the measurements taken before and after eye drop application (all P > 0.05). In the left eyes, SFCT changed by 5.8 ± 22.2 μm (examiner 1), 5.5 ± 36.5 μm (examiner 2), and 3.9 ± 29.5 μm (examiner 3), respectively, and the midperipheral choroidal thickness changed by -6.9 ± 47.9 μm (examiner 1), -3.5 ± 28.7 μm (examiner 2), and 16.0 ± 28.2 μm (examiner3), respectively, without significant differences between baseline and study end (all P > 0.05). Application of cyclopentolate 1% and of pilocarpine 1% did not result in a statistically significant change in choroidal thickness in young healthy adults.
Gesehen am 24.07.2025